Methodical instructions to independent work of students on the discipline "Organizational and technical support of audit on professional safety of workplaces in the field of occupational safety" - Yevtushenko, N. S.; Tverdokhliebova, Natalia Yevheniivna (My University, 2023)
Organization of an audit of occupational safety of workplaces, laboratory studies of working conditions, assessment of technical condition of production equipment for certification of workplaces for compliance with regulations on labor protection in the manner and time prescribed by law, and the results of measures to eliminate dangerous and harmful to health of industrial factors will contribute to improving occupational safety and health.
Keywords: methodical instructions; labor protection; labor protection audit; working conditions; labor safety